2016
DOI: 10.1038/srep31406
|View full text |Cite
|
Sign up to set email alerts
|

A hole inversion layer at the BiVO4/Bi4V2O11 interface produces a high tunable photovoltage for water splitting

Abstract: The conversion of solar energy into hydrogen fuel by splitting water into photoelectrochemical cells (PEC) is an appealing strategy to store energy and minimize the extensive use of fossil fuels. The key requirement for efficient water splitting is producing a large band bending (photovoltage) at the semiconductor to improve the separation of the photogenerated charge carriers. Therefore, an attractive method consists in creating internal electrical fields inside the PEC to render more favorable band bending f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 42 publications
2
31
1
1
Order By: Relevance
“…Notably, pristine FTO/BiVO 4 photoanodes (prepared under 0.1 mbar with removed V 2 O 5 ) generated a lower photocurrent than photoanodes consisting of the BiVO 4 @Bi 4 V 2 O 11 heterojunction. It has been already reported that such a system positively affects the photoelectroactivity in comparison to bare BiVO 4 [31,36]. The geometry of the system should be taken into account, as it was discussed for the BiVO 4 /V 2 O 5 photoanode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, pristine FTO/BiVO 4 photoanodes (prepared under 0.1 mbar with removed V 2 O 5 ) generated a lower photocurrent than photoanodes consisting of the BiVO 4 @Bi 4 V 2 O 11 heterojunction. It has been already reported that such a system positively affects the photoelectroactivity in comparison to bare BiVO 4 [31,36]. The geometry of the system should be taken into account, as it was discussed for the BiVO 4 /V 2 O 5 photoanode.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of heterojunction leads to the inhibition of bulk electron/hole recombination [38]. Generally, the presence of type-II heterojunction enhances bulk e − /h + separation efficiency due to the internal electric field generated on the phases interface, e.g., BiVO 4 /Bi 4 V 2 O 11 [36]. The enhancement of photoactivity in the case of the Bi 4 V 2 O 11 -containing photoanode may be also related to improved charge transfer resistance through the photoactive film in comparison with pristine BiVO 4 as it was reported previously [22].…”
Section: Resultsmentioning
confidence: 99%
“…The illuminated open-circuit potential (OCP) is a feasible way for determining V fb when sufficient light is illuminated to remove band bending. This technique is an effective and convenient way to obtain the V ph of the electrode and gives useful information about the band bending and is commonly measured by increasing the light intensity until the J ph saturates [46]. Figure 7 depicts the OCP versus the illumination intensity to the samples of p-GaAsPN cell, MDMP-PPV:PCMB (bulk heterojunctions consisting of polyf2-methoxy-5-s38,78-dimethyloctyloxyd-pphenylenevinylene (MDMO-PPV) and 6,6-phenyl C61-butyric acid methyl ester PCBM), dye-sensitized solar cell (DSSC) (ITO/CuPc/C 60 /BPen/Al) and polycrystalline Si.…”
Section: Illuminated Open-circuit Potential (Ocp)mentioning
confidence: 99%
“…et al, who introduced an efficient approach which is coupling ferroelectric materials with semiconductors to boost the photovoltage higher than that obtainable from a conventional p-n heterojunction. The ferroelectric Bi 4 V 2 O 11 perovskite and n-type BiVO 4 creates a virtual p-n junction that produces high photovoltage of 1.39 V ( Figure 8j) [46]. The metal-insulator-semiconductor (MIS) photoanode using silicon was fabricated by Digdaya et al [57].…”
Section: Illuminated Open-circuit Potential (Ocp)mentioning
confidence: 99%
“…Nanostructures of Bi 2 WO 6 , [77] Bi 2 MoO 6 , [78] Bi 2 O 2 CO 3 , [79] BiOX (X = Cl, Br,I ), [80][81][82] Bi 2 S 3 [83] and BiVO 4 [84] were synthesized as photocatalysts to decompose organic pollutants under visible-light irradiation. Although various methods, such as composite photocatalysts, noble metal loading and interfacial electric field, were used to improve the photocatalytic efficiency of bismuth-based photocatalysts, [84][85][86] the materials still demonstrate low quantum yields leadingt o www.chemphotochem.org low photocatalytic efficiencies. Therefore, buildinga ni nternal electric field in the crystal structure of photocatalystsi sa ne fficient strategy to greatlyi mprove charges eparationt oo btain materials with ahighq uantum yield.…”
Section: Layer-structure Polar Photocatalystsmentioning
confidence: 99%